High‐Resolution Thermophysical Analysis of the OSIRIS‐REx Sample Site and Three Other Regions of Interest on Bennu. Issue 6 (24th June 2022) - Rozitis, B.; Ryan, A. J.; Emery, J. P.; Nolan, M. C.; Green, S. F.; Christensen, P. R.; Hamilton, V. E.; Daly, M. G.; Barnouin, O. S.; Lauretta, D. S.
Abstract: The OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer) spacecraft sampled asteroid (101955) Bennu on 20 October 2020 and will return the collected regolith to Earth in 2023. Before sample collection, spectral observations of four regions of interest on Bennu's surface were acquired at high spatial resolution (2–9 m per spectrometer spot) to identify the most suitable site for sampling and provide contextual information for the returned sample. In this study, we investigate thermal‐infrared (6–50 μm) observations of these four regions, including the site that OSIRIS‐REx ultimately sampled, using the Advanced Thermophysical Model with input digital terrain models derived from laser altimetry. From model‐to‐measurement comparisons, we find that the observed brightness temperatures depend strongly on small‐scale topography, local variations in thermal inertia, and the observation phase angle. Thermal inertia mapping reveals spatial variations that distinguish the different boulder types found on Bennu. A boulder bearing carbonate veins has higher thermal inertia than average, suggesting that cementation processes reduced its porosity. The thermal inertia of the site sampled is 190 ± 30 J m −2 K −1 s −1/2, which is consistent with observations of a fine‐grained regolith mixed with porous rocks. Thermophysical modeling of the site sampled predicts that the maximum temperatures experienced by the collected sample while on Bennu were 357 ± 3 and 261 ± 3 K for the surface and 50 cm depth, respectively. We predict that OSIRIS‐REx will return a sample with thermophysical properties unique from those of meteorites. Plain Language Summary: Thermal inertia is a physical characteristic of materials that, along with topography, controls how the surface temperature of a planetary body changes from day to night. On asteroids like Bennu, the target of the Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS‐REx) sample return mission, thermal inertia is dictated by several properties of the surface, such as the porosity and abundance of boulders and the size of smaller particles. Thermal inertia is quantified by running numerical simulations of asteroid surface temperatures and comparing the results to the observed temperatures collected by a thermal‐infrared instrument onboard the OSIRIS‐REx spacecraft. Here, we ran a very high‐resolution temperature model, using topographic data from an onboard laser altimeter, for each site on Bennu that the OSIRIS‐REx mission considered sampling. The resulting local maps of thermal inertia distinguish boulders with different surface textures and porosities. The thermal inertia of the site that OSIRIS‐REx sampled is consistent with the observed presence of both small particles and porous boulders. The predicted maximum temperatures experienced by the collected samples while on Bennu imply that any ancient organic compounds will have undergone only minimal alteration by heating from the Sun. We expect the returned samples to be unique among meteorites, based on their distinct thermal properties. Key Points: Brightness temperatures of select sites on Bennu acquired at 2–9 m spatial scales depend on topography, thermal inertia, and phase angle Thermophysical modeling using digital terrain models of these sites finds diversity in thermal inertia among boulders The site where regolith was sampled has a thermal inertia of 190 ± 30 J m –2 K –1 s –1/2, consistent with fine grains mixed with porous rocks